Repurposing Poloxamers as Antimicrobial Agents: A Comprehensive Review of Mechanisms and Applications - Peña Corona, Sheila I.; Borbolla‐Jiménez, Fabiola V.; Duarte‐Peña, Lorena; Moreno, Angélica; Pérez‐Caltzontzin, Luis E.; Del Prado‐Audelo, María Luisa; Romero‐Montero, Alejandra; González‐Torres, Maykel; Cortés, Hernán; Hernández‐Parra, Hector; Sharifi‐Rad, Javad; Leyva‐Gómez, Gerardo (Drug development research, 2025)
ABSTRACT In the last decades, the misuse and overuse of antimicrobial medications have precipitated the appearance of antimicrobial resistance, a phenomenon associated with around 4.95 million deaths per year worldwide. Control of this resistance represents the biggest challenge for antimicrobial therapies and novel drug formulations. Poloxamers are nonionic synthetic triblock copolymers used as excipients for formulating antibiotics, mainly as emulsifying agents, gelling agents, surfactants, and humectants. It has been discovered that poloxamers may have antimicrobial activity as microbicides or micro biostatics or can also potentiate other germicide drugs' efficacy. This review aims to examine the use of poloxamers and synthesize their potential mechanisms of action as antimicrobial drugs for treating microbial infections. This review's methodology included sourcing articles from PubMed, Google Scholar, and Scopus, using specific medical subject headings terms to warranty precision and pertinence. Poloxamer action mechanisms include quorum sensing inhibition, cellular membrane disruption, bacterial biofilm inhibition, and disruptions in bacteria cell walls. Results of Molecular docking demonstrated that poloxamers could interact directly with active sites of adhesion proteins and alter their functioning. Our experimental tests showed that poloxamers 188 and 407 possess the potential to be antimicrobial agents by effectively inhibiting Staphylococcus aureus and Pseudomonas aeruginosa growth. Despite the convincing evidence, further research is required to overcome challenges related to poloxamers' bioavailability and establish effective dosing regimens for different poloxamers to warrant their use and safety as antimicrobial drugs.